2020
DOI: 10.9734/ajaees/2020/v38i730378
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Adoption of Fuel-efficient Stove in Dessie Zuria Woreda, Amhara Regional State, Ethiopia

Abstract: The three-stone fire stove is inefficient in converting solid fuels to energy and, it only yields 5 up to 20 per cent of the overall thermal efficiency. Fuel-efficient stoves are expected to contribute to the environment, economic and health sectors by achieving sustainability in the energy sector. Therefore, due to the benefits of the fuel-efficient stoves, the need to study factors influencing the adoption of these stoves are becoming more important. The study aimed to assess factors influencing the adoption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This indicates that, as individuals become more aware of the benefits of the ICS, the probability of adopting that Tikikil stove increases. The finding of this study agreed with related studies (Sheha and Makame, 2017;Kassa et al, 2020) who demonstrated that the level of awareness had a positive and significant influence on the adoption of improved energy-saving ICS. Therefore, this study suggests that raising the awareness level of rural households would help them to decide on the adoption and sustained use of more energy-efficient ICS.…”
Section: Binary Logit Model Estimation Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that, as individuals become more aware of the benefits of the ICS, the probability of adopting that Tikikil stove increases. The finding of this study agreed with related studies (Sheha and Makame, 2017;Kassa et al, 2020) who demonstrated that the level of awareness had a positive and significant influence on the adoption of improved energy-saving ICS. Therefore, this study suggests that raising the awareness level of rural households would help them to decide on the adoption and sustained use of more energy-efficient ICS.…”
Section: Binary Logit Model Estimation Resultssupporting
confidence: 92%
“…This implies that households who are far away from the nearby town are less likely to adopt the Tikikil stove than households who are near the town. This finding is in line with the works of (Legesse et al, 2015;Kassa et al, 2020) who found that the distance from nearby town affects significantly and negatively the adoption of ICS.…”
Section: Binary Logit Model Estimation Resultssupporting
confidence: 92%